Cervical cancer screening in a population of black South African women with high HIV prevalence: A cross-sectional study - Joyce Sikwese Musonda; Pumla Pamella Sodo; Olalekan Ayo-Yusuf; Elizabeth Reji; John Musonda; Langalibalele Honey Mabuza; John Velaphi Ndimande; Jimmy Akii; Olufemi Babatunde Omole (Public Library of Science (PLoS), 2022)
Cervical cancer is largely preventable through early detection, but screening uptake remains low among black women in South Africa. The purpose of this study was to determine the prevalence and factors associated with cervical cancer screening in the past 10 years among black African women in primary health care (PHC) clinics, in Gauteng Province, South Africa. This was a cross-sectional study involving 672 consecutively recruited black women at cervical cancer screening programs in PHC clinics between 2017 and 2020. An interviewer-administered questionnaire covered socio-demographics, HIV status, sexual history, cervical cancer risk factors knowledge, and screening behaviours in the past 10 years. The mean age of participants was 38 years. More than half (63%) were aged 30-49 years. Most completed high school education (75%), were unemployed (61%), single (60%), and HIV positive (48%). Only 285 (42.4%) of participants reported screening for cervical cancer in the past 10 years. Of participants that reported receiving information on screening, 27.6% (n = 176) and 13.97% (n = 89) did so from healthcare facilities and community platforms respectively. Participants aged 30 years or more were more likely to report for cervical cancer screening as compared to other categories in the past 10 years. The study found low cervical cancer screening prevalence. This calls for health education campaigns and prevention strategies that would target individual patients' contexts and stages of behavioral change. Such strategies must also consider socio-demographic and clinical correlates of cervical cancer screening and promote better integration into PHC services in South Africa.